1 kHz Remote Control of a Balancing Robot with Wi-Fi-in-the-Loop. Issue 2 (2020) - Branz, Francesco; Antonello, Riccardo; Pezzutto, Matthias; Tramarin, Federico; Schenato, Luca
Abstract: Countless industrial applications can potentially benefit from the implementation of wireless control systems, leading to a widespread research effort to investigate new solutions in the field. Nevertheless, currently available wireless communication standards for industrial automation are not able to achieve high control frequencies. In particular, time–critical applications (e.g. industrial robotics and manipulation) require high sampling frequencies to be properly implemented. The higher throughput provided by IEEE 802.11 (Wi-Fi) can theoretically tame critical applications, although reliability is a key issue. In this work Wi-Fi is adopted to increase the achievable control rates up to 1 kHz, while reliability is guaranteed by mitigating communication flaws through model–based estimation techniques. The core of the proposed approach relies on a modified Kalman filter that exploits a buffer of incoming measures to account for delayed data packets. The proposed solution is validated through a hardware– in–the–loop experiment that features actual Wi-Fi hardware and a commercial embedded PC board. The obtained results give a preliminary, yet valuable, validation of the proposed approach testing the solution on relevant hardware.